2008
DOI: 10.1111/j.1467-7652.2008.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of aprotinin, a therapeutic protease inhibitor, into the thylakoid lumen of genetically engineered tobacco chloroplasts

Abstract: SummaryAprotinin, a bovine protease inhibitor of important therapeutic value, was expressed in tobacco plastid transformants. This disulphide bond-containing protein was targeted to the lumen of thylakoids using signal peptides derived from nuclear genes which encode lumenal proteins. Translocation was attempted via either the general secretion (Sec) or the twin-arginine translocation (Tat) pathway. In both cases, this strategy allowed the production of genuine aprotinin with its N-terminal arginine residue. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…Aprotinin, a bovine protease inhibitor, was targeted to the lumen of thylakoids of tobacco plastid transformants using thylakoid signal peptides derived from nuclear genes which encode luminal proteins (Tissot et al 2008). Plastid-encoded pre-Tic40 was properly processed and targeted and assembled into a functional complex at the inner membrane of chloroplast (Singh et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Aprotinin, a bovine protease inhibitor, was targeted to the lumen of thylakoids of tobacco plastid transformants using thylakoid signal peptides derived from nuclear genes which encode luminal proteins (Tissot et al 2008). Plastid-encoded pre-Tic40 was properly processed and targeted and assembled into a functional complex at the inner membrane of chloroplast (Singh et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In most reports, which include an insecticidal toxin expressed at 46% tsp (De Cosa et al, 2001), or a GFP expressed at 38% tsp (Yabuta et al, 2008), no obvious phenotypic defect, such as growth retardation, has been observed in plastid transformants. When phenotypic modifications were noted, these were directly linked to the specific properties of the expressed transgenes (Tregoning et al, 2003;Magee et al, 2004;Ruiz and Daniell, 2005;Chakrabarti et al, 2006;Hasunuma et al, 2008;Tissot et al, 2008). Only in the case of lysin was the hyperexpression of the recombinant protein reported to limit plant development by exhausting the protein synthetic capacity of chloroplasts (Oey et al, 2009).…”
mentioning
confidence: 99%
“…The transplastomic plant lines with the transgene expression cassette controlled by the strong constitutive ribosomal RNA operon promoter showed distinct growth retardations and mild pigment deficiency. In many cases, plastid expression of recombinant proteins does not result in abnormal phenotypes, but an increasing number of studies has reported phenotypic alterations in transplastomic plants (Lössl et al 2003;Magee et al 2004;Scotti et al 2015;Tissot et al 2008;Tregoning et al 2003;Waheed et al 2011). The two main reasons underlying pigment deficiency or a delay in plant development are toxicity of the transgene product due to interference of the recombinant protein with essential processes in the chloroplast (e.g.…”
Section: Discussionmentioning
confidence: 99%